Lithological and Foraminiferal Characteristics of Shoreface and Shallow Shelf Facies off Bogue Banks, NC - Howie, Lillian C (East Carolina University, 2018)
Fossil foraminiferal assemblages are used by paleontologists to determine the depositional environment of the strata in which the assemblages are found. This allows for the reconstruction of past environments and climates working under the assumption that specific foraminiferal assemblages are diagnostic to the depositional environment. However, foraminiferal assemblages of several coastal subenvironments (e.g., beach, shoreface, ebb tide delta, inner shelf) have yet to be extensively studied. In this study, Holocene sediments from vibracores taken off the coast of Bogue Banks, NC, were analyzed for their lithology and foraminiferal assemblages to study the differences before shoreface and inner shelf environments. Two 3 m vibracores from each environment were logged using a method that is independent from composition, and samples of sediment from Holocene units were taken for foraminiferal analysis. Sand and mud content were determined by sieving. The 63-710 micron fraction of the samples were floated in a sodium polytungstate solution to concentrate foraminiferal tests. Approximately 100 specimens were randomly picked from each sample and the relative percentages of three major foraminiferal taxonomic groups were recorded. In shelf sediment samples, assemblages comprised 95% to 100% Rotaliina. By comparison, in shoreface sediment samples, assemblages comprised 85% to 90% Rotaliina, with 10% to 15% Miliolina. These results suggest that a potential method for distinguishing the two subenvironments could be found in the presence of absence of genera within the suborder Miliolina.
Keywords: paleontology; North Carolina; environmental science